O que se sabe, se ensina e se aprende sobre a matemática: estudo das representações sociais dos sujeitos do PROEJA do IFRJ - Silva, Albertina Maria Batista de Sousa da (2020)
The present research had as object of study social representations of the students and professors of the National Program of Integration of Professional Education with Basic Education in the Modality of Education of Youth and Adults - PROEJA - in reality of the Federal Institute of Education Science and Technology of Rio de January - IFRJ - and on Mathematics in professional training. We present educational practices in the field of mathematics teaching; we verify how the subjects perceive mathematics in professional training and we identify the materialization of mathematical content for professional training. The research was based on Serge Moscovici's Theory of Social Representations of 1961 (1978, 2008, 2010, 2012 and 2015), and on Denise Jodelet's approaches to social representations (1984, 1989, 2001 and 2007). For the construction of the characteristics of the empirical field we use some authors: Gaudêncio Frigotto (2005, 2008 and 2011), Maria Ciavatta (2003, 2005 and 2011), Jaqueline Ventura (2011), Jane Paiva (1981 and 2009), Vanilda Paiva (2015). With regard to mathematical education, we elected: Ubiratan D’Ambrosio (2012), Dario Fiorentini (2005) and Ole Skovsmose (2013). In the relationship between mathematical education and social representations, we opted for Abreu (1995) Ponte (2007) and Machado and César (2012). Questionnaires, interviews, focus groups and the systematization of data relied on the software CHIC and Iramuteq. We support content analysis in Laurence Bardin (1977) and Maria Laura Franco (2008). Students and teachers from the Maintenance and Computer Support course at the Duque de Caxias, Nilópolis and Rio de Janeiro campuses participated. The analytical path related the dimensions of the Theory of Social Representations, the emerging categories and the five research axes (role of institutional agents and overcoming actions, EJA teacher training, content/organization/selection/curriculum, social representation, knowledge/utility). For the students, the social representations about Mathematics in professional training reverberate as being complex and difficult to learn. It needs to be meaningful to work in the world of work and that educational practices, teacher training, teacher understanding of the modality and dialogue contribute to learning. The teachers' social representations of the mathematics taught in the course reveal that there is a contribution to professional training. They affirm the difficulty in mobilizing mathematical knowledge and attribute the students' teaching trajectory to influence in the construction of their mathematical thinking. In response to our thesis, the set of knowledge, values and perceptions of the subjects of EJA on mathematics, confronted with formal school practice, produces significant changes that raise the mathematical scientific knowledge. However, students do not gain the representative theoretical repertoire to operate on reality, since what makes learning possible is the concept of reality. Regarding Mathematical Education, the research presented a field of interest for future studies, specifically, teaching and learning at EJA